Analisis Penerapan Digital Marketing sebagai Strategi Pemasaran UMKM - Eva Yuniarti Utami; Kartika Sari; Eva Desembrianita; Basnendar Herry Prilosadoso; Rudy Irwansyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Marketing strategy for MSMEs (Micro, Small, and Medium Enterprises) is a plan designed to promote and sell products or services offered by MSMEs. This study aims to analyze the application of digital marketing as a marketing strategy for MSMEs. This research method uses qualitative techniques, which can be applied in journals that consider the application of digital marketing as a marketing strategy for Micro, Small, and Medium Enterprises (MSMEs) can include a case study approach. The data used in this study are interview data, as well as internal documents such as sales reports and operational changes, which can provide a deep understanding of the real impact of digital marketing on MSME operations and competitiveness. The results of the study found that digital marketing strategies for MSMEs (Micro, Small, and Medium Enterprises) are very important for increasing visibility, expanding reach, and attracting new customers. By implementing this digital marketing strategy, MSMEs can more easily develop their business, reach a wider audience, and increase sales effectively. The key is consistency and a deep understanding of the target market you want to reach.